Determining the Private Universities’ Competitiveness Using Multidimensional Scaling: A Case Study from Indonesia - Zulkarnain Siregar (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2021)
The competition in attracting potential and targeting students also rises highlighting that the more popular the university, the higher its reputation and competitiveness in the eyes of many. In addition, the competitiveness of the university is reflected in the quality of graduates and the competency of human resources attached to the universities. Extant literature suggests that human resources, strategic planning, leadership, and infrastructures are key elements in determining the university’s performance. In Indonesia, the university’s performance can be found in the achievement of the university upon three main responsibilities of education, research, and community service This study quantifies the universities individual impression on human resources, strategic planning, leadership, infrastructure, and the university’s three main responsibilities of education, research, and community service called as Tri Dharma Perguruan Tinggi using Multidimensional Scaling (MDS). MDS in this study aims to visualize the underlying dimensions in further explaining similarities or dissimilarities (distances) among the five variables from the Resource Based-View Theory’s point of view. The data collection method is organized using questionnaires distributed to those 250 respondents. Multidimensional scaling is used to analyze the level of similarity of individual cases of human resources, strategic planning, leadership, infrastructures, and Tri Dharma Perguruan Tinggi among private universities in the province of Sumatera Utara, Indonesia. Based on the analysis using MDS, the study shows leadership in Human Resources, Strategic Planning, Tridharma, and Infrastructure variables. The subsequent test on the model fit involving five tested variables highlighted a good model fit with the RSQ score at .98082 (98.082%) and the matrix stress coefficient at .05240. Based on the MDS test result, we can conclude that strong leadership and relevant infrastructures are essential for private universities in the Province of Sumatera Utara to gain a good reputation and competitiveness at their best. Leadership and Infrastructures are statistically identical as the availability of world-class infrastructures in supporting the academic activities in universities is determined by a strong leader who will manage the decision-making as soon as he/she can for the relevant purposes